Antes de De rebus Hispaniae. La primera versión de la batalla de Las Navas de Tolosa de Rodrigo Jiménez de Rada - Martín Alvira (E-Spania)
The Cistercian Lectionary of Las Huelgas Abbey includes a liturgical office commemorating the Battle of Las Navas de Tolosa (the “Feast of the Holy Cross”), which reproduces an account of the victory of 1212 seems to be written by the Archbishop of Toledo Rodrigo Jiménez de Rada in his De rebus Hispaniae. This study aims to demonstrate that this version of the Battle is the very first account, composed by Archbishop Rodrigo himself soon after the battle took place and rewriten later by himself to incorporate his famous historical work.